Effectiveness of postharvest treatment with salicylic acid and mineral nutrients in the control of gray mould rot of strawberry (Indian Journal of Arid Horticulture, 2025)
Strawberry (Fragaria x ananassa) is a non- climacteric fruit with a very short postharvest life. Loss of quality in this fruit is mostly due to its relatively high metabolic activity and sensitivity to fungal decay (Hernandez-Munoz et al., 2008). Grey mold, caused by Botrytis cinerea Pers. Fr., is the most economically significant postharvest pathogen of strawberry fruits. The use of synthetic chemical fungicides has been the main method for reducing postharvest disease. However, consumer concern over pesticide residues on foods, along with pathogen resistance to many currently used pesticides, has increased the need to find alternative methods for decay control (Karlidag et al., 2009).
Keywords: Fragaria x ananassa; Botrytis cinerea; pesticide; postharvest